Multiscaling analysis of ferroelectric domain wall roughness - Guyonnet, J. (2012)
Using multiscaling analysis, we compare the characteristic roughening of ferroelectric domain walls in Pb(Zr0.2Ti0.8)O3 thin films with numerical simulations of weakly pinned one-dimensional interfaces. Although at length scales up to LMA ≥ 5 μm the ferroelectric domain walls behave similarly to the numerical interfaces, showing a simple monoaffine scaling (with a well-defined roughness exponent ζ), we demonstrate more complex scaling at higher length scales, making the walls globally multiaffine (varying ζ at different observation length scales). The dominant contributions to this multiaffine scaling appear to be very localized variations in the disorder potential, possibly related to dislocation defects present in the substrate.